Effects of addition of mola at different densities on production of giant freshwater prawn (Journal of the Bangladesh Agricultural University, 2012)
The effects of mola (Amblypharyngodon mola) at different densities in polyculture with freshwater prawn (Macrobrachium rosenbergii) were investigated at the Fisheries Field Laboratory, Bangladesh Agricultural University,  Mymensingh. The experiment had three treatments, viz. prawn + 1 mola m-2, prawn + 1.5 mola m-2 and prawn + 2 mola m-2 and were treated as T1, T2, and T3, respectively with three replications in each. Prawn stocking density was  same (3 juvenile m-2) in all treatments. Feeds were applied twice daily for prawn. Assuming 80% survival, feeding  rates were gradually reduced to 10-5% of body weight from the beginning to the last month. Water quality parameters  (except transparency, chlorophyll-a) did not vary significantly (P>0.05). Weight gain, SGR (% body weight), gross and  net production of prawn were not significantly different (P>0.05). Higher total production was recorded in T3 (574.61  ±39.58 kg ha-1) followed by TI (531.65±42.40 kg ha-1) and T2 (514.75±77.91 kg ha-1). It was found that addition of  mola at different densities had no effects on survival and production performance of prawn. Therefore, nutrient-dense mola may be stocked as an additional species with freshwater prawn. It might be concluded that treatment T3 was better proposition for prawn-mola polyculture. DOI: http://dx.doi.org/10.3329/jbau.v10i1.12109 J. Bangladesh Agril. Univ. 10(1): 163167, 2012